Enhancement of hydrosolubility and in vitro antiproliferative properties of chalcones following encapsulation into β-cyclodextrin/cellulose-nanocrystal complexes. Issue 15 (1st August 2019) - Rioux, Benjamin; Pouget, Christelle; Ndong-Ntoutoume, Gautier M.A.; Granet, Robert; Gamond, Aurélie; Laurent, Aurélie; Pinon, Aline; Champavier, Yves; Liagre, Bertrand; Fagnère, Catherine; Sol, Vincent
Graphical abstract: Abstract: This paper describes the preparation of two chalcone/β-cyclodextrin/cellulose-nanocrystals complexes and the study of their antiproliferative activities against two colorectal and two prostatic cancer cell lines. The aim of this work was to enhance hydrosolubility of chalcones thanks to the hydrophilic character of cellulose nanocrystals. These latter were linked, through ionic interactions, to a cationic derivative of β-cyclodextrins whose lipophilic cavity allowed the encapsulation of hydrophobic chalcones: 3-hydroxy-3′, 4, 4′, 5′-tetramethoxychalcone (1 ) and 3′, 4, 4′, 5′-tetramethoxychalcone (2 ). First, we showed that encapsulation allowed hydrosolubilization of chalcones. Then, chalcone/β-cyclodextrin/cellulose-nanocrystals complexes demonstrated enhanced in vitro antiproliferative activities, compared to the corresponding free-chalcones.